Enhancing the Stability Characteristics of the Compliant Vertical Access Riser Using the Effects of Riser Damping and Axial Tension - Tochukwu Chukwuka Oraelosi; Solomon Chukwuka Nwigbo; Sunday Madubueze Ofochebe; Obiora B. Ezeudu (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
In this paper, practical ways to enhance the stability characteristics and vibration response of the compliant vertical access riser (CVAR) system are studied. The CVAR system is proposed for a floating production system operating in water field of nominal depth 2438m. The study utilized a state-space model of the riser motion developed from semi-discretization of the governing equation of motion by Galerkin’s method. The stability analysis proceeds from a desirable static state of the riser system found in literature. Performance of the CVAR system under mode-coupling condition is studied exclusively, to account for the effects of damping and axial tension. The study found that the stability of the CVAR system is improved when the axial tension or the damping is increased, however, the level of improvement achievable through independent adjustment of these variables is limited and short of the field requirement. To achieve a sustainable stability for a CVAR system operated under adverse weather condition, the combined effects of increased riser damping and tension could be utilized. In the present case, about 100% increase in axial tension, from the static equilibrium condition, is required of the CVAR system with damping coefficient of 0.5, to increase the minimum critical platform heave amplitude from a nominal value to a desirable value , over the excitation frequency range.